The Velvet Proteins VosA and VelB Play Different Roles in Conidiation, Trap Formation, and Pathogenicity in the Nematode-Trapping Fungus Arthrobotrys oligospora - Zhang, Guosheng; Zheng, Yaqing; Ma, Yuxin; Yang, Le; Xie, Meihua; Zhou, Duanxu; Niu, Xuemei; Zhang, Ke-Qin; Yang, Jinkui (Frontiers in Microbiology, 2019)
The velvet family proteins VosA and VelB are involved in growth regulation and differentiation in the model fungus Aspergillus nidulans and other filamentous fungi. In this study, the orthologs of VosA and VelB, AoVosA and AoVelB, respectively, were characterized in the nematode-trapping fungus Arthrobotrys oligospora, which captures nematodes by producing trapping devices (traps). Deletion of the AovelB gene resulted in growth defects in different media, and the aerial hyphae from the ΔAovelB mutant lines were fewer in number and their colonies were less dense than those from the wild-type (WT) strain. The ΔAovelB mutants each displayed serious sporulation defects, and the transcripts of several sporulation-related genes (e.g., abaA, flbC, rodA, and vosA) were significantly down-regulated compared to those from the WT strain. Furthermore, the ΔAovelB mutant strains became more sensitive to chemical reagents, including sodium dodecyl sulfate and H2O2. Importantly, the ΔAovelB mutants were unable to produce nematode-capturing traps. Similarly, extracellular proteolytic activity was also lower in the ΔAovelB mutants than in the WT strain. In contrast, the ΔAovosA mutants displayed no obvious differences from the WT strain in these phenotypic traits, whereas conidial germination was lower in the ΔAovosA mutants, which became more sensitive to heat shock stress. Our results demonstrate that the velvet protein AoVelB is essential for conidiation, trap formation, and pathogenicity in A. oligospora, while AoVosA plays a role in the regulation of conidial germination and heat shock stress.